Investor Legitimate Expectation and Indirect Expropriation in Domestic Regulation Concerning the Application of Domestic Raw Application - Muchammad Zaidun; Yuniarti; Widhayani Dian Pawestri (Universitas Airlangga, 2022)
Law No 11/2020 concerning Job Creation (Omnibus Law’) mandates the use of domestic raw materials for all industries in Indonesia. Following the passage of the Omnibus Law, Indonesia issued Government Regulation No 28/2021 concerning Industrial Management and Presidential Regulation No 12/2021 concerning the amendment of Presidential Regulation No 16/2018 concerning Government Procurement of Goods and Services. Both regulations oblige all industries in Indonesia to use domestic raw materials pursuant to the Omnibus Law. In investment law, this kind of policy could lead to indirect expropriation because when an investor makes an investment in a host country, the raw material and machines for production might come from their home state or other states. Furthermore, a public-private partnership contract with investors funding infrastructure projects for at least 50 years using materials agreed upon in advance will lead to indirect expropriation. The method used in this research was legal research theory with statute and conceptual approaches. From this research, the policy of the Indonesian government can be described as indirect expropriation because the regulation is effective and enforced.